A NOTE ON CARMICHAEL’S CONJECTURE - Andrade, Antonio A.; Cundari, Guilherme Z. (Academic Publications, 2022)
Euler’s totient function (also known as Euler’s '-function or just Euler’s function) was introduced by Leonhard Euler (1707-1783) in 1760, motivated by a problem proposed by Pierre of Fermat (1607-1665). Given a positive integer n, in this work, we present new results about the existence of a positive integer m such that φ(m) = φ(n).
Keywords: Carmichael’s conjecture; Euler function; Prime number